Birth models that work - Davis-Floyd, Robbie; Barclay, Lesley; Tritten, Jan; Daviss, Betty-Anne (University of California Press, 2009)
This groundbreaking book takes us around the world in search of birth models that work in order to improve the standard of care for mothers and families everywhere. The contributors describe examples of maternity services from both developing countries and wealthy industrialized societies that apply the latest scientific evidence to support and facilitate normal physiological birth; deal appropriately with complications; and generate excellent birth outcomes—including psychological satisfaction for the mother. The book concludes with a description of the ideology that underlies all these working models—known internationally as the midwifery model of care.